The Fractured Marketplace for Standardized Testing - Haney, Walter M. author. aut Link
XIV, 347 p.
Keywords: Standardized testing in the United States has been increasing at a rapid pace in the last twenty-five years. The market for tests has not only been expanding rapidly, but has also been changing sharply in structure into a fractured marketplace. Indeed, one of the main features of this book is that the market for standardized testing is highly fractured - with segments of the market facing monopoly conditions, others facing oligopoly conditions and still others where near free-market conditions exist. One of the main premises of the book is that the structures of markets have strong implications for how those markets perform. While this notion is widely accepted among economists, it is not widely appreciated in educational research. A second motivation for the book is that very little scholarly attention has been focused on the standardized testing industry. This topic - the structure of the testing industry and implications for the quality of tests and test use - affects how we evaluate the learning of students, the effectiveness of teaching, the quality of schools and the educational health of the nation. Of particular concern to the authors is one vital aspect of test quality: test validity. This book is the most current and authoritative review and analysis of the market for standardized testing.